Challenges and Opportunities for Septage Management in the Urban Areas of Indonesia â Case Study in Bandung City - Pham Ngoc Bao; Muhammad Sonny Abfertiawan; Pankaj Kumar; Muhammad Fahmi Hakim (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Because of the burgeoning urban population, there is huge pressure on both natural resources and basic urban infrastructure, especially sewerage systems, with Indonesia as no exception. It is estimated that about 95% of human waste in Indonesia ends up untreated or partially treated in septic tanks before being discharged in the natural environment, contaminating the living environment as well as adversely affecting human health and economic development. This study conducted a comprehensive investigation on septage management in Bandung City, Indonesia, to gain a better understanding of the challenges and opportunities for improved performance of on-site sanitation systems as well as septage management across its sanitation service chain. The results showed that the following issues are the main reasons behind poor sanitation in Bandung city: a) poor design and construction of septic tanks with no or only partial lining, resulting in leaking (>90% of septic tanks are malfunctioning); b) irregular desludging, i.e. about 2/3 of population desludge their septic tanks only once in more than 5 years; c) lack of proper guidelines and awareness about the benefits of regular monitoring and operation of septic tanks; d) lack of good sanitation service providers; and e) lack of funds for building sufficient capacity of septage treatment plants.